Factors Associated With Caregiver Burden in Family Caregivers of Older Adults: A Cross-Sectional Study - Hande Kaya Akdoğan; Nesrin İlhan (AVES, 2024)
Aim: This study aimed to assess caregiver burden and identify factors associated with caregiver burden among family caregivers of older adults. Method: This cross-sectional study included 140 older adults and their family caregivers. The study was conducted between February and November 2020 at a hospital in İstanbul. Data were collected using the Zarit Burden Interview (ZBI), Multidimensional Scale of Perceived Social Support (MSPSS), General Health Questionnaire-12 (GHQ-12), and Katz Activities of Daily Living Scale (Katz ADL). Results: The mean age of the caregivers was 49.20 ± 10.75 years, and 72.9% were female. The mean ZBI score was 30.65 ± 9.31. Katz Activities of Daily Living Scale (β = −.579, p < .001), older adults' age (β = −.462, p < .001), caregiver's gender (β = .250, p < .001), MSPSS (β = −.195, p < .01), whether the caregiver had regular health check-ups (β = −.156, p < .05), and GHQ-12 (β = .147, p < .05) were found to be significant predictors of caregiver burden respectively. These variables explain 56.3% of the total variance for the caregiver burden (R2 = .563, p < .001). Conclusion: Being a female caregiver and experiencing poor mental health were associated with a higher caregiver burden. Regular health check-ups received by caregivers and good social support were associated with a lower caregiver burden. Older age and higher dependency of older adults were associated with a lower caregiver burden. Based on these findings, there is a need for interventions and social policies aimed at reducing caregiver burden among family caregivers of older adults.